KAJIAN YURIDIS PUTUSAN MAHKAMAH AGUNG NO.1402K/PDT/2015 (STUDI KASUS HAK MILIK NO.947 KELURAHAN SRIWEDARI - HERMAWAN, BAMBANG (Dinamika Hukum, 2018)
The disclosure of cases relating to the lawsuit against the holder of the certificate by the holder of the original land rights, has raised a sense of insecurity for the holders of the certificate. In Surakarta City there was a dispute over the cancellation of the second / substitute certificate, namely the Right of Ownership No. 947 of the Village. Under these circumstances, it encourages the author to know how legal certainty is the land title certificate for the implementation of a court decision that has permanent legal force, which is later canceled by the Supreme Court's decision and to find out how the protection provided by the law against the party registered in the right certificate replacement land. This study uses a normative juridical approach, by examining and reviewing the applicable and competent laws and regulations to be used as a basis for problem solving and using information from several resource persons as reference material. From the results of the study it can be seen that the issuance of a replacement certificate / second ownership rights No. 947 Sriwedari Village based on a court decision that has permanent legal force, namely the Supreme Court Decision No. 1402k / Pdt / 2015, has not been able to provide full legal certainty and legal protection to rights holders. Because with a negative publication system, there are still opportunities to file state administrative claims / disputes by other parties. Keywords: Land Registration, Certificate Cancellation